Complete chloroplast genome of the orchid Cattleya crispata (Orchidaceae: Laeliinae), a Neotropical rupiculous species - Perini, Violeta da Rocha; Leles, Bruno [UNESP]; Furtado, Carolina; Prosdocimi, Francisco (Taylor & Francis Ltd, 2016)
A partial genome dataset was sequenced for the orchid Cattleya crispata using both Illumina and 454 technologies. The chloroplast genome was assembled using iterative runs of MIRA software that yielded a circular molecule with 148,343 bp in length and deposited in GenBank database ( Accession Number KP168671). The plastid genome conserved the quadripartite structure present in most Orchidaceae chloroplasts and was composed by 79 protein-coding genes, 39 tRNAs and 8 rRNAs. Genome structure, gene order and orientation were similar to previously described chloroplasts for Cymbidium orchids, differing in gene order for petN and psbM genes. Data described here contain the first report of a complete chloroplast for the Neotropical subtribe Laeliinae and may contribute to improve the phylogenetic resolution and allow the development of new molecular markers for population genetic studies of orchids.
Keywords: Espinhaco; next-generation-sequencing; orchid; plastid genome; rock outcrop